Characterization of Collagen from Swim Bladder Waste of Yellow-pike (Muraenesox talabon) by Acid and Hydrothermal Extraction - I Wayan Darya Kartika; Wini Trilaksani; I Ketut Mudite Adnyane (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractIndonesian capture fisheries production reached ± 6.4 million tons in 2014. This number was predictedresulted a huge fishery waste, one of them was swim bladder that potentially contain collagen, so it needs tobe developed. This aim of this study was to determine the characteristics of the swim bladder (proportionand chemical content) and collagen characteristics (yield and physicochemical properties) extracted fromthe swim bladder cunang (Muraenesox talabon). Swim bladder waste had proportion 0.57 to 0.67% of wholeyellow-piked conger body weight and 24.74% protein/100 g wet weight (equivalent to 93.39% of protein/100gram dry). The waste had a potency of collagen, which is characterized by the high proportion of theamino acids glycine, proline, hydroxyproline and alain. Acid extraction and hydrothermal process resultedcollagen extracts, identified from a spectrum of amide I, amide II and amide III functional groups. Collagenextracted with acid process contained a higher glycine than hydrothermal one, but instead hydrothermalprocess produced extract with a higher proline, hydroxyproline and alanine composition.